Impact of home factors on students’ reading achievements - Elijio, Aistė (Lietuvos matematikos rinkinys, 2004)
On the basis of PIRLS 2001 data, we consider the impact of factors characterizing the home situation of students to their reading literacy achievements. The data was analyzed for three groups of countries: Eastern Europe, ``Northern’’, and English-speaking countries. Parents’ education, home educational resources, and early home literacy activities have a similar influence in all these groups of countries, while the financial well-being of the family and the type of location of a school have rather different influences in the groups.